Tradition, modernism, and apartheid - D. Goosen (Acta Theologica)
In this article it is argued that apartheid, as idea-historical phenomenon, needs to be understood against the background of a short comparison between modern and premodern thought. Apartheid was, in many respects, a theoretical and practical manifestation of modernism. As such, it was by no means a modern anomaly, or a phenomenon that contradicted the fundamental assumptions of modern philosophical and political thought. The first section of this article addresses only a single aspect of traditional thought, namely the idea of being understood as circular event. Traditional thought understood being as emanating from, and returning to a first principle, namely the Good (Plato), the One (Plotinus), or God (Aquinas). The ensuing section discusses only a single aspect of modernism, namely its understanding of being not as circular event, but as a neutral, spatial, and linear grid upon which reality can be mapped. Once mapped on such a grid, according to modernism, being can be experienced as a “standing reserve” (or as an always available resource) to be controlled and used at will by the modern subject. In the third section of this article, it is argued that apartheid was made possible by the above ontological presupposition. According to the apartheid state, being could, in principle, be spatialised on a neutral grid, and thus directed and controlled from the vantage point of the sovereign subject. The concluding section focuses on the much-discredited community, the Afrikaners. Despite disclaimers among Afrikaners, the heavy burden of the apartheid legacy rests squarely on their shoulders. However, it will also be argued that Afrikaners, if given the opportunity, may provide us in future with important examples of a politics that moves beyond the spatialising and geometrising ambitions of the modern state. In a hermeneutical re-appropriation of their own pre-modern tradition, Afrikaners may, in collaboration with other communities, help show a way toward a traditional politics of place (rather than the modern politics of space).